Experiences of global Islamic microfinance practices: lessons learnt and way forward - Kassim, Salina; Kassim, Siti Nadhirah; Othman, Nadhrah (International Journal of Engineering and Technology, 2018)
Despite the increasing need for microfinance services that are shariah-compliant among the Muslims, growth of the Islamic microfinance industry has not been as encouraging as that of the conventional counterpart. Islamic microfinance accounts for a mere 0.5% of global microfinance, amid the absence of a cost-efficient service model. As a result, financial inclusion rate in most Muslim countries stands at only 27%, with religious requirement being quoted as one of the important obstacles. This study intends to evaluate the current practices of several leading Islamic microfinance institutions globally and learn from their experiences and best practices in efforts to further improve the Islamic microfinance industry in the future.Â Â